Identification and characterization of Cardiac Glycosides as senolytic compounds - Francisco Triana-Martínez (Nature Portfolio, 2019)
Senolytic compounds have the ability to eliminate senescent cells from tissues and have been shown to be beneficial in various animal models of age-related diseases. Here the authors show that cardiac glycosides commonly used for heart diseases have senolytic properties in humanized mouse models of tumorigenesis and lung fibrosis.